The relationship between demographic factors, psychological distress, COVID worries, resilience, and athletic identity: A study of collegiate student-athletes - Shinnick, R.; Filho, E. (Asian Journal of Sport and Exercise Psychology, 2024)
The COVID-19 pandemic provided athletes with an entirely new unforeseen circumstance, as many collegiate sport events and seasons were halted or canceled, forcing athletes into premature and non-normative retirement from sport. In the current study we analyzed the relationship between demographic factors, psychological distress, COVID worries, resilience, and athletic identity while controlling for student-athletes` year of eligibility and NCAA division. Three-hundred and twenty-five student-athletes (232 females; 88 males; 5 non-binary) participated in the study by completing a demographic survey, the Athletic Identity Measurement Scale, the Brief Resilience Scale, the Depression Anxiety Stress Scale-21, and the COVID-specific worries questionnaire, which were administered electronically through a Qualtrics survey link. A stepwise hierarchical regression analysis revealed that (a) being either a senior (ß = -0.15, p = .03) or a junior (ß = -0.12, p = .01) was associated with lower levels of athletic identity; and (b) higher psychological distress scores were positively related to athletic identity (ß = 0.14, p = .01). A path analysis revealed that resilience predicted psychological distress (ß = -0.159, p = .01), which in turn predicted both COVID worries (ß = 0.43, p < .01) and athletic identity (ß = 0.12, p = .03).